The role of hypoxia-inducible factors in metabolic diseases. Issue 1 (December 2018) - Gonzalez, Frank; Xie, Cen; Jiang, Changtao
Abstract Hypoxia-inducible factors (HIFs), a family of transcription factors activated by hypoxia, consist of three α-subunits (HIF1α, HIF2α and HIF3α) and one β-subunit (HIF1β), which serves as a heterodimerization partner of the HIFα subunits. HIFα subunits are stabilized from constitutive degradation by hypoxia largely through lowering the activity of the oxygen-dependent prolyl hydroxylases that hydroxylate HIFα, leading to their proteolysis. HIF1α and HIF2α are expressed in different tissues and regulate target genes involved in angiogenesis, cell proliferation and inflammation, and their expression is associated with different disease states. HIFs have been widely studied because of their involvement in cancer, and HIF2α-specific inhibitors are being investigated in clinical trials for the treatment of kidney cancer. Although cancer has been the major focus of research on HIF, evidence has emerged that this pathway has a major role in the control of metabolism and influences metabolic diseases such as obesity, type 2 diabetes mellitus and non-alcoholic fatty liver disease. Notably increased HIF1α and HIF2α signalling in adipose tissue and small intestine, respectively, promotes metabolic diseases in diet-induced disease models. Inhibition of HIF1α and HIF2α decreases the adverse diet-induced metabolic phenotypes, suggesting that they could be drug targets for the treatment of metabolic diseases. This Review focuses on the function of hypoxia-inducible factors (HIFs) in controlling metabolism and their influence in metabolic diseases (including obesity, type 2 diabetes mellitus and non-alcoholic fatty liver disease). The therapeutic potential of targeting HIFs for the treatment of metabolic diseases will also be discussed. Key points Obesity triggers hypoxia in adipose tissue and the small intestine, which stabilizes and activates hypoxia-inducible factor (HIF)1α and HIF2α signalling, resulting in adverse metabolic effects, including insulin resistance and non-alcoholic fatty liver disease. Induction of HIF1α in adipocytes, through a suppressor of cytokine signalling 3 (SOCS3)–signal transducer and activator of transcription 3 (STAT3) axis, leads to the upregulation of inflammation and downregulation of adiponectin expression, resulting in insulin resistance. Activation of HIF2α in the small intestine increases expression of sialidase 3, resulting in an elevation of small intestinal and serum levels of ceramides that in turn potentiate obesity-associated metabolic diseases. Genetic or chemical inhibition of HIF1α and HIF2α signalling in adipose tissue and the small intestine ameliorates obesity-associated metabolic diseases, indicating that they could be targeted for treatment of metabolic disorders.